Viruses in the female lower reproductive tract: a systematic descriptive review of metagenomic investigations - Layla Honorato; Heuder Gustavo Oliveira Paião; Antonio Charlys da Costa; Tânia Regina Tozetto-Mendoza; Maria Cássia Mendes-Correa; Steven S. Witkin (npj Biofilms and Microbiomes)
Abstract The lower female reproductive tract (FRT) hosts a complex microbial environment, including eukaryotic and prokaryotic viruses (the virome), whose roles in health and disease are not fully understood. This review consolidates findings on FRT virome composition, revealing the presence of various viral families and noting significant gaps in knowledge. Understanding interactions between the virome, microbiome, and immune system will provide novel insights for preventing and managing lower genital tract disorders.